Export performance Malaysian furniture industry: rethinking competitiveness - Haque, A. K. M. Ahasanul (medi+WORLD Internationa, 2014)
Abstract Malaysia is one of the ten largest furniture exporting countries of the world. Behind the success of this industry there are several competitive advantages which are rare and difficult to copy by its competing nations. Hence the importance of measuring competitive advantages of the furniture industry of Malaysia has arisen. The concept ‘competitiveness’ is vast and vital for a nation to measure. The purpose of this paper includes, specifying the meanings and measurements of ‘competitiveness’. After that the study will clarify the definitions of ‘competitiveness’ for the furniture industry of the country. ‘Competitiveness’ of any industry should be measured based on the appropriate objectives of any nation. In the measurements, the expectations of involved exporters, importers or clients and the worldwide demand and supply conditions should be brought under consideration which cannot be possible by a single measure of competitiveness.